MULTIVARIABLE DAMAGE ANALYSIS FOR FIBER-REINFORCED COMPOSITES - Pysarenko, Alexander (SWorld-Ger Conference proceedings, 2025)
Damage detection and assessment in carbon-fiber-reinforced polymer (CFRP) composites is challenging because of their anisotropic and heterogeneous nature. Their damage progression is complex, involving multiple failure modes like matrix cracking, fiber-ma